Human apolipoprotein C1 transgenesis reduces atherogenesis in hypercholesterolemic rabbits. (March 2021) - Gautier, Thomas; Deckert, Valérie; Aires, Virginie; Le Guern, Naig; Proukhnitzky, Lil; Patoli, Danish; Lemaire, Stéphanie; Maquart, Guillaume; Bataille, Amandine; Xolin, Marion; Magnani, Charlène; Masson, David; et al.
Abstract: Background and aims: Apolipoprotein (apo) C1 is a 6.6 kDa protein associated with HDL and VLDL. ApoC1 alters triglyceride clearance, and it also favors cholesterol accumulation in HDL, especially by inhibiting CETP in human plasma. Apart from studies in mice, which lack CETP, the impact of apoC1 on atherosclerosis in animal models expressing CETP, like in humans, is not known. This study aimed at determining the net effect of human apoC1 on atherosclerosis in rabbits, a species with naturally high CETP activity but with endogenous apoC1 without CETP inhibitory potential. Methods: Rabbits expressing a human apoC1 transgene ( HuApoC1Tg ) were generated and displayed significant amounts of human apoC1 in plasma. Results: After cholesterol feeding, atherosclerosis lesions were significantly less extensive (−22%, p < 0.05) and HDL displayed a reduced ability to serve as CETP substrates (−25%, p < 0.05) in HuApoC1Tg rabbits than in WT littermates. It was associated with rises in plasma HDL cholesterol level and PON-1 activity, and a decrease in the plasma level of the lipid oxidation markers 12(S)-HODE and 8(S)HETE. In chow-fed animals, the level of HDL-cholesterol was also significantly higher in HuApoC1Tg than in WT animals (0.83 ± 0.11 versus 0.73 ± 0.11 mmol/L, respectively, p < 0.05), and it was associated with significantly lower CETP activity (cholesteryl ester transfer rate, −10%, p < 0.05; specific CETP activity, −14%, p < 0.05). Conclusions: Constitutive expression of fully functional human apoC1 in transgenic rabbit attenuates atherosclerosis. It was found to relate, at least in part, to the inhibition of plasma CETP activity and to alterations in plasma HDL. Graphical abstract: Image 1 Highlights: Transgenic rabbits expressing human apoC1 ( HuApoC1Tg ) were successfully generated. Atherosclerotic lesions were less extensive in HuApoC1Tg rabbits. HDL-C levels and HDL size were increased in HuApoC1Tg rabbits. CETP activity was reduced and PON-1 activity was increased in HuApoC1Tg rabbits.